Al-Imlā’ Tiqniyyah fa’ālah li Kasyf al-Musykilāt wa al-Ḥulūl fi Ta’līm al-Lugah al-‘Arabiyyah - Ahmad Maghfurin; Siti Nafisah; Asmaa Abusamra (Arabic Education Program IAIN Pekalongan, 2021)
This research aims to extrapolate the weaknesses of students at SMP (Junior High School) Sadamiyyah-Jepara. The dictation test method is used to obtain data about error types of student answers. Data analysis is carried out through two phases: identifying errors, and then searching for their source. The research found several problems facing students at SMP Sadamiyyah in writing dictated texts. The most important are those related to writing Arabic letters, understanding vocabulary, grammars, and the overall meaning of sentences used in the dictation process. One causes these problems is the nature of Arabic writing, and the other is due to their lack of listening and their weakness in Arabic. The sound varies with its symbols in some Arabic words, the proximity of the source of some letters also inherits the difficulty of distinguishing between them. In addition, the lack of vocabularies and grammars hinders the overall understanding of the meanings of sentences. Dictation is a test of arabic comprehensive ability. Therefore, improving students’ ability in the dictation requires a lot of language practices. Students' poor in dictation becomes a starting point for reforming the Arabic language education process integratively.